IKLIM KOMUNIKASI ORGANISASI PSIS SEMARANG PADA MASA PANDEMI COVID-19 - Devanada Bulan Aldizza; Hedi Pudjo Santosa (Interaksi Online, 2022)
The coronavirus disease or Covid-19 has contributed to the large disruption in all aspects of life, including the sports sector, specifically football. In an effort to reduce the spread of the virus, various global soccer matches or trainings had to be postponed. Moreover, communication in the football sector must also be limited due to the Covid-19 pandemic, as in Indonesian football organizations, particularly PSIS Semarang. This research was intended to describe the communication climate of the PSIS Semarang organization during the Covid-19 pandemic. This research was classified as a qualitative descriptive research. The data of this research were successfully obtained by means of interviews with seven members of PSIS Semarang who were involved as informants. The results showed that the communication pattern used in PSIS Semarang was a bottom-up pattern with a positive communication climate accompanied by a sense of kinship. The communication climate in PSIS Semarang during the Covid-19 pandemic was a good and positive climate by members of the organization because of their mutual respect, motivation, and encouragement for organizational members to be better. The existence of a good communication climate makes members of the organization feel comfortable and form good interactions with fellow members of the organization. Barriers to organizational communication at PSIS Semarang during the Covid-19 pandemic included the lack of communication intensity, the emergence of misunderstandings, and network constraints.